Modeling the metabolic adaptations of the biomass under rapid growth and starvation conditions in the activated sludge process. Issue 6 (1st November 2005) - Lavallée, B; Lessard, P; Vanrolleghem, P A
Abstract : For wastewater treatment, the activated sludge models (ASMs) 1, 2, and 3 of the International Water Association (IWA) are accepted as industrial standard. However, many authors have observed that the kinetic parameters of these models depend on the type of substrate, process configuration, and sludge age. Some publications showed that the kinetic parameters of ASMs could be influenced by regulation of enzyme production. Therefore, an engineer aiming to make some modifications to a specific system is not able to predict the response of the real system after the modifications and choose the right configuration or modifications with the same set of parameters. On the other hand, cybernetic models are proposed for modeling cell growth and focus, among other things, on regulation of enzyme production, that is to say on induction. Thus, the objective of this paper is to present an activated sludge model that mimics the enzymatic induction of active biomass within the framework of ASMs. In the proposed model, process rates are modulated according to the environmental conditions and cell history. The model is fitted on the basis of data found in the literature. All data collected from short and long transient experiments were fitted with the same set of parameters, which was not possible with other models. The proposed model gives a more realistic picture of active biomass and of its specific activity under highly varying process conditions, but further research is required to support the model with experimental data. Key words : activated sludge models (ASMs), activity, biomass, enzymes, induction, model, parameter, rate, regulation, sludge, transient.